Comparison of lipid-lactate levels between brain abscesses and brain tumors through magnetic resonance spectroscopy examination - Syafa, Nahdah Ardelia; Fatmawati, Heni; Putri, Komang Yunita Wiryaning; Hairrudin; Adji, Novan Krisno (Faculty of Medicine, Universitas Islam Indonesia, 2024)
Background: Intracranial masses are masses found in the intracranial space, such as brain abscesses and brain tumors. Magnetic Resonance Spectroscopy (MRS) examination is a noninvasive examination procedure with magnetic resonance regarding chemical composition or metabolites. One of the metabolites examined in MRS is lipid-lactate which will appear or increase if there are certain abnormalities such as in abscesses and brain tumors.Objective: This study analyzed the difference in lipid-lactate levels between brain abscess and brain tumor through MRS examination.Methods: This research adopted an observational analytic approach with a cross-sectional design. Samples in this study were brain abscess and brain tumor patients examined using MRI and MRS at Siloam Jember Hospital from June 2018 to October 2023. The sampling method employed encompassed a total sampling of 45 patients with 15 brain abscesses and 30 brain tumors. Results: The results of this study showed that the lipid-lactate levels of all brain abscess patients increased by 15 patients (100%), while in brain tumors, lipid-lactate levels increased by 19 patients (63.3%) and decreased by 11 patients (36.7%). The mean rank of lipid-lactate levels in brain abscesses was 14101,93 while in brain tumors was 6220,69. The statistical analysis results using the Mann-Whitney comparison test obtained a p-value of 0.008 (<0.05), meaning there is a significant difference.Conclusion: There is a significant difference in lipid-lactate levels in brain abscesses and brain tumors.